Virtual assessment: using in-game behaviors during immersive role-play for contextually relevant assessment of fear of intimacy - Qian, Yijun; Lin, Luoying; Li, Yaning; Wang, Zhimeng; Li, Meng; Tong, Xin; LC, RAY (Frontiers in Virtual Reality, 2025)
Fear of Intimacy (FOI) affects approximately 2.5% of the population, posing diagnostic and treatment challenges relying on time-consuming psychotherapy, self-reported scales, and clinical interviews. This study addresses these clinical hurdles by exploring Virtual Reality’s (VR) potential in assessing FOI. Through simulating intimate scenarios and gathering context-based data, we investigate whether participants’ VR behaviors correlate with FOI and attachment insecurities, specifically avoidance and anxiety. Our findings reveal significant correlations between in-game behaviors and Fear of Intimacy Scale (FIS) scores, notably in avoidance tendencies following exposure to couple-conflict audio. Gender-specific effects are evident, with females exhibiting closeness-anxiety correlations and males displaying distinct fear responses. These results hold significant relevance for understanding FOI assessment challenges. Furthermore, our study underscores the potential of VR to predict avoidance tendencies based on in-game behaviors, while informing the design of gender-specific VR experiences for enhanced clinical assessment outcomes and patient experiences.